Premenstrual syndrome incidence rate and risk factors among the working population in the Republic of Korea: a prospective cohort study - Wanhyung Lee; Seunghyun Lee; Joonho Ahn; Ryoon Sun Lee; Seong-Kyu Kang (BMC, 2022)
Abstract Background Premenstrual syndrome (PMS) is the most common disease of the genitourinary tract in women. Although a sizeable proportion of women have symptoms or diagnosed PMS, its etiology remains unclear. The purpose of this cohort is to offer incidence and relevant risk factors of PMS among reproductive-aged Korean female workers. Methods Cohort data used were from the National Health Insurance Service-Female Employees (from 2007 to 2015) conducted by the NHIS. A total of 121,024 female workers were analyzed to estimate the incidence and hazard ratio of PMS. PMS data was based on information obtained from medical facility visits during an eight-year follow-up. Results The incidence of PMS was 7.0% during follow-up periods. In industrial classification, human health and social work activities have the highest incidence (9.0%) of PMS. Cumulative incidence of PMS has continuously increased by approximately 1% annually for eight years. Adjusted hazard ratio with 95% confidence interval was significantly higher in the 15-19 years old age group (2.81, 95%CI 2.35-3.36), manual worker (1.06, 95%CI 1.01-1.12), with anemia (1.13, 95%CI 1.06-1.20), and underweight (1.21, 95%CI 1.10-1.25) compared to those in the reference group. Conclusion This study describes the PMS status with trend and risk factors using follow-up design among women under a middle-aged working population. Further study is warranted for better understanding on the risk factors of PMS for reproductive-aged female workers.